A PORTRAIT OF RELIGIOUS VALUES IN AN ELT TEXTBOOK FOR JUNIOR HIGH SCHOOL: A CRITICAL DISCOURSE ANALYSIS - Falin, Erina Ismalia; Suharjito, Bambang; Fitriani, Ika (ELLTER Journal, 2025)
In a society with diverse religious backgrounds, Indonesian students need to understand the steps to investigate various problems in every aspect of life-related to differences in language, culture and religion. Therefore, English text books as a medium for teaching students not only contain differences between one individual and another but also broadly cover several dimensions of relationships between several parties. Through documentary studies, this research focused on the religious content of the ELT textbook published by the Ministry of Education and Culture. In addition, Critical Discourse Analysis was used to investigate the religious values ​​depicted in the ELT textbook aimed at junior high school students. Three dimensions of the relationship between religious values have ​​appeared in the textbook, namely: (1) the individual relationship with God; (2) individual relationships with other people; and (3) the individual relationship with the universe (environment). These three dimensions are represented by inserting visual-verbal and textual artifacts or products containing religious values ​​in the ELT textbook. This indicates that English plays an important role in shaping students' character. Thus, English teachers are expected to be able to integrate these religious values ​​to increase the positive impact on students' academic quality.